Global Value Chain: The Effects of Trade Mechanism on Energy Efficiency using Simultaneous Equation: Evidence from Asian Countries within Belt and Road - Acquah, Mensah Patience; Bonsu, Mandella Osei Assibey; Atampokah, Rosemond (Business and Economic Research, 2021)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">Long-term economic development is thought to necessitate the use of energy. To sustain steady economic growth, economies have increased their dependence on energy sources, tightened restrictions, and put pressure on energy supplies. Our paper employed simultaneous equations with GMM and SBM model to examine the impact of trade mechanism on energy efficiency of Asian countries within the Belt and Road Countries. We find significant increase in energy efficiency. After controlling the heterogeneous effects, the magnitude impact of the coefficient was noticeably which approves that the heterogeneity of countries and years influence the empirical findings of the model. Further, we find and validates that trade in the GVC mechanism helps to promote energy efficiency. Energy efficiency could be greatly promoted by emphasizing its significance in the age of GVC. Several policy recommendations support the findings